Struktur Teks Ekspositori: Representasi Visual Strategis dalam Meningkatkan Keterampilan Pemahaman Membaca Peserta Didik - Patricia Mae Oteda; Argelle Kay Fabellon; Cathy Mae Dabi Toquero (Musamus Journal of Primary Education, 2021)
Expository Text Structure strategy addresses the informational structure of the text that provides students with a feasible way to analyze through a visual representation of the text which creates an understanding of the basic part of the expository text. This study was carried out through a quasi-experimental design or two group pre-test post-test designs to determine the effectiveness of the Expository Text Structure strategy on the reading comprehension of the students. The researchers developed a reading comprehension test to gather data and were analyzed using percentage rate, frequency count, percentage mean, and t-test for independent samples. Results revealed an increase in the result of the experimental group than the control group after the application of the intervention. Therefore, there was a difference in the reading comprehension level of the pupils in both groups. The change between pre-test and post-test scores of both groups was significantly different. Hence, the study concluded that the Expository Text Structure strategy was significantly effective in enhancing the reading comprehension skills of the students. This offers pedagogical implications such that the Expository Text strategy can be applied to increase the comprehension of the students.